If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-5 + 6x) = 129 (-5 * 3 + 6x * 3) = 129 (-15 + 18x) = 129 Solving -15 + 18x = 129 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 18x = 129 + 15 Combine like terms: -15 + 15 = 0 0 + 18x = 129 + 15 18x = 129 + 15 Combine like terms: 129 + 15 = 144 18x = 144 Divide each side by '18'. x = 8 Simplifying x = 8
| V=1/3~r2(h) | | -x-8=x+4 | | 3m^2n+12mn^2=0 | | 5.2(3+3x)-1.6=14 | | -2x-1=2x+7 | | 3=3x+1 | | 3(-5+2x)=9 | | X+6.3+5.6+8.4=27.4 | | 3.23-3.14x=2x-3.195 | | 7(-6-2x)=98 | | 2.5x+1.1=4.5 | | 10=2/3d | | 1.3x+8.8=3.1x-2 | | 10(3+x)=15(x-1)+1 | | -2/5-6 | | X^2+box+1=0 | | 12x+11+25x+2+69=360 | | 110=48-5x+7 | | -2x-1=x+20 | | 12x+11+25x+2=360 | | 10=-8(2x^2-2x-1) | | Cos^2x+6cosx+6=0 | | (X+9)(x-19)=0 | | 6(9+x)=102 | | 9-3+5x=9+4x | | 2(-4+x)=10 | | 4y+92=196 | | 2(1x-10)=-44 | | 4x(6x-8)= | | 30x+45=90 | | 2x(1x-10)=-44 | | 7(1x-2)=49 |